Bladder cancer mortality and private well use in New England: an ecological study. Issue 2 (13th January 2006) - Ayotte, Joseph D; Baris, Dalsu; Cantor, Kenneth P; Colt, Joanne; Robinson, Gilpin R; Lubin, Jay H; Karagas, Margaret; Hoover, Robert N; Fraumeni, Joseph F; Silverman, Debra T
Abstract : Study objective: To investigate the possible relation between bladder cancer mortality among white men and women and private water use in New England, USA, where rates have been persistently raised and use of private water supplies (wells) common. Design: Ecological study relating age adjusted cancer mortality rates for white men and women during 1985–1999 and proportion of persons using private water supplies in 1970. After regressing mortality rates on population density, Pearson correlation coefficients were computed between residual rates and the proportion of the population using private water supplies, using the state economic area as the unit of calculation. Calculations were conducted within each of 10 US regions. Setting: The 504 state economic areas of the contiguous United States. Participants: Mortality analysis of 11 cancer sites, with the focus on bladder cancer. Main results: After adjusting for the effect of population density, there was a statistically significant positive correlation between residual bladder cancer mortality rates and private water supply use among both men and women in New England (men, r = 0.42; women, r = 0.48) and New York/New Jersey (men, r = 0.49; women, r = 0.62). Conclusions: Use of well water from private sources, or a close correlate, may be an explanatory variable for the excess bladder cancer mortality in New England. Analytical studies are underway to clarify the relation between suspected water contaminants, particularly arsenic, and raised bladder cancer rates in northern New England.